Pemanfaatan Teknologi Informasi dan Komunikasi Dalam pelaksanaan Kurikulum 2013 di MI Tarbiyatul Athfal - Uswatun Hasanah (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2021)
Information and communication technology (ICT) has advantages over traditional methods in effectiveness and efficiency. Mastering ICT is one of the most important competencies possessed by educators. The purpose of this research is to study how the use of "information and communication technology" (ICT) is used as the implementation of the 2013 curriculum at MI Tarbiyatul Athfal, as well as the supporting and inhibiting components of the use of ICT in the implementation of the 2013 curriculum. This is a “qualitative descriptive” research project. . Research data collection is done through observation, interviews, and documentation. According to the findings of this study, ICT was used in the implementation of the 2013 curriculum at MI Tarbiyatul Athfal by providing ICT facilities to assist the process of “learning planning, learning implementation, and assessment of learning outcomes”. ICT also supports instructors in the “learning process”, enabling learning materials to be more “interesting, innovative, and active” to be presented. In addition, the use of ICT has helped achieve the objectives of the 2013 curriculum. Budget allocation policies for the procurement of ICT facilities, as well as the presence of Wi-Fi network routers that spread throughout the school buildings, are supporting aspects. Physical and non-physical factors are obstacles to the use of ICT in the implementation of the 2013 curriculum.